If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5abx = 30ac * c Multiply ac * c 5abx = 30ac2 Solving 5abx = 30ac2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-30ac2' to each side of the equation. 5abx + -30ac2 = 30ac2 + -30ac2 Combine like terms: 30ac2 + -30ac2 = 0 5abx + -30ac2 = 0 Factor out the Greatest Common Factor (GCF), '5a'. 5a(bx + -6c2) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(bx + -6c2)' equal to zero and attempt to solve: Simplifying bx + -6c2 = 0 Solving bx + -6c2 = 0 Move all terms containing a to the left, all other terms to the right. Add '-1bx' to each side of the equation. bx + -1bx + -6c2 = 0 + -1bx Combine like terms: bx + -1bx = 0 0 + -6c2 = 0 + -1bx -6c2 = 0 + -1bx Remove the zero: -6c2 = -1bx Add '6c2' to each side of the equation. -6c2 + 6c2 = -1bx + 6c2 Combine like terms: -6c2 + 6c2 = 0 0 = -1bx + 6c2 Simplifying 0 = -1bx + 6c2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
a = {0}
| -13=-3+2a | | 2/3-4=5 | | 6(x+5)=x | | 9x+1/5 | | 0=9x^2+89x+239 | | -3=-3+c | | 9-4(2x-7)=50 | | 0=9x^2+89+239 | | u/5=-3/10 | | 3=-3+3x | | -2=4+3z | | 8=-5+z/-6 | | 5pm+4(4p+6)+6= | | (12a^7b^-4)/4a^-8b^5 | | -2=4+32 | | 2x+2x-1+x=14 | | 1/3=3/4-5x/6 | | 3(x-4)=6x-9-3x | | 7v=-20 | | Y=.25x-12 | | 7y=-2x-5 | | 9(m+2)= | | 0=-3+10x | | 0.65x+0.05(4-x)=0.10(86) | | x+200+x+500=x+x+200+100+x+200 | | 6x+3y=3600 | | 5=-21v | | -2-3=-5+c | | (x+2/5)+(x+6/3)=3 | | 8/3x=-16 | | (5-j/16)/(j-5/10) | | Y^2-14y+33= |